Long-term outcome of patients followed by nephrologists after an acute tubular necrosis episode - Brito, G. A. [UNESP]; Balbi, André Luis [UNESP]; Abrão, Juliana Maria Gera [UNESP]; Ponce, Daniela [UNESP] (Hindawi, 2012)
Aims of our study were to describe the long-term survival in patients surviving an acute tubular necrosis (ATN) episode and determine factors associated with late mortality. We performed a prospective cohort study that evaluated the long-term outcome of 212 patients surviving an ATN episode. Mortality at the end of followup was 24.5%, and the probability of these patients being alive 5 years after discharge was 55%. During the followup, 4.7% of patients needed chronic dialysis. Univariate analysis showed that previous CKD (P = 0.0079), cardiovascular disease (P = 0.019), age greater than 60 years (P < 0.0001), and higher SCr baseline (P = 0.001), after 12 months (P = 0.0015) and 36 months (P = 0.004), were predictors of long-term mortality. In multivariate analysis, older age (HR = 6.4, CI 95% = 1.2-34.5, P = 0.02) and higher SCr after 12 months (HR = 2.1, 95% CI 95% = 1.14-4.1, P = 0.017) were identified as risk factors associated with late mortality. In conclusion, 55% of patients surviving an ATN episode were still alive, and less than 5% required chronic dialysis 60 months later; older age and increased Scr after 12 months were identified as risk factors associated with late death. © 2012 G. A. Brito et al.